Uridine-Derived 4-Aminophenyl 1-Thioglucosides : DFT Optimized FMO, ADME, and Antiviral Activities Study - Mohammad Atiqur, Rahman; Unesco, Chakma; Ajoy, Kumar; Md. Rezaur, Rahman; Mohammed Mahbubul, Matin (Biointerface Research in Applied Chemistry, 2023)
The biological roles of carbohydrates, especially their synthetic glycoconjugates, are at the forefront of research, and their applications and research are in the development of an impressive area of carbohydrate-derived vaccines. Considering this, several thioglucosides 2-6 conjugated with paraaminophenyl and uridine moieties are investigated for their possible application as hepatitis antiviral applications. Geometry optimization of these uridine thioglucosides by density functional theory (DFT) indicated that their glucopyranose rings are in 4C1 chair conformation with β-glucosidic linkage. Frontier molecular orbital (FMO), molecular electrostatic potential (MEP), lower hardness, and softness calculations indicated their higher electrophilic nature. Solubility and ADMET studies indicated that the uridine thioglucosides might be safer drugs to use. With these encouraging results, molecular docking of 2-6 was conducted with hepatitis C virus (HCV, 3su4) and hepatitis B virus (HBV, 5e0i) proteases where the binding affinities for 2-6 were found higher than the standard anti-hepatitis drug sofosbuvir. Overall, the thioglucosides showed a better binding affinity with HBV protease (5e0i) than the HCV protease (3su4), indicating their prospect against these viruses.